Increasing productivity of water: A requirement for food and environmental security - Molden, David J.; Rijsberman, Frank; Matsuno, Y.; Amarasinghe, Upali A. (2002)
Working paper 1 of the Dialogue on Water, Food and Environment, 2001. The complete article is available on the CD-ROM version of this Annual Report or at www.iwmi.org/dialogue